Metode Enterprise Architecture Planning Untuk Merencanakan Sistem Informasi Manajemen Anggaran Perguruan Tinggi Swasta - Anton Wahyu Nugroho; Setiyowati Setiyowati; Andriani Kusumaningrum (Jurnal Ilmiah SINUS, 2020)
The success of higher education can be seen from the performance of education, research and community service, and university governance. The use of information technology is very influential in organizational performance. Budget management and expenditure are some of the important business processes in a university involving several work units so that integration system is needed. The purpose of this study is to plan an Enterprise Architecture budget and information system of expenditure management that is integrated with systems in other work units. An Enterprise Architecture Planning (EAP) is a methodology for making enterprise architecture planningby focusing on data management architecture, application creation architecture, and technology architecture. Those will be used as well as the implementation of architecture to support the achievement of organizational goals, namely integration system. The results of this study are Blue Print of Architecture Enterprise budget and expenditure management information systems in Higher Education. This Blue Print of Enterprise Architecture information system includes several business processes, namely business processes, budget management, payroll, asset management, HR management, and attendance. This compiled architecture is still found gap. For example, there are still entities that must be added (add), retained (replaced), replaced (removed) and removed (remove), with details of 17 Added entities, 1 Retained entity, 14 Replaced entities, and 0 Removed entity. In conclusion, the total gap is 32 entities.